Workplace Activity in Health Professionals Exposed to Chemotherapy Drugs: An Otoneurological Perspective - Fernandes,Natália Martinez (2016)
Abstract Introduction The manipulation of antineoplastic drugs presents high risk for accidents and occupational diseases. Objective To evaluate the auditory and vestibular systems of workers who are exposed to chemotherapeutic treatment in the University Hospital of Universidade Federal de Santa Maria, Brazil, and to identify the use of individual protection equipment, related to the obtained results. Methods This study is a cross-sectional study using a quantitative method. We evaluate 33 male and female workers, ranging from 21-60 years old, of the nursing and pharmacy sectors. The workers underwent conventional Audiologic Assessment; Transient Evoked Otoacoustic Emissions; and Computerized Vectoelectronystagmography. Results The majority of the sample was female (90.9%). Individual protection equipment was used by 90.9% of the workers. Complaints of dizziness were reported by 56.25% of nursing workers and 52.94% of pharmacy workers. Audiological and vestibular assessment results were within normal limits, 96.97% and 74.20%, respectively. However, audiometric configuration of notch type was identified in 75.75% of all workers. Audiometric notches (76%) and altered caloric test (100%) were often associated with decreased use of coal masks. Conclusion Among the workers evaluated, the vestibulocochlear system was within the normal limits. The presence of notch configuration indicates the need to use individual protection equipment.